Non-surgical organ preservation and new technologies in laryngeal radiation - Dietz, Andreas; Eckel, Hans; deVries, Alexander; Brunner, Markus (Frontiers in Oncology, 2025)
The term “larynx organ preservation” (LOP) has become a synonym for non-surgical laryngeal cancer treatment based on chemotherapy and radiation multimodality therapy [simultaneous chemoradiation (CRT) or neoadjuvant chemotherapy followed by radiotherapy (NCT+RT)]. Currently, the distinction between good and bad candidates for LOP is not clear, and the decision for surgical or non-surgical treatment depends on the patient’s needs and desires, the experience and recommendation of the surgeon, the philosophy of the institution, and others. Nevertheless, the major disadvantage of LOP by CRT and NCT+RT is the potential need for salvage surgery due to tumor persistence after the application of full per-protocol treatment. Head and neck surgeons worldwide complain that in principle, salvage surgery is frequently possible after CRT but causes major complications and is not feasible in a relevant number of patients. While NCT+RT is globally used to select responders for LOP, NCT alone has not been shown to improve overall survival. Therefore, this procedure has lost its influence in standard head and neck cancer treatment beyond LOP. Recently, NCT as part of the perioperative transoral surgical treatment concept in head and neck cancer is gaining interest again. In addition to conventional chemotherapy, the combination with immune checkpoint inhibitors as a neoadjuvant concept has shown to be effective in non-controlled trials by opening a new door of encouraging treatment options for LOP.